2020
DOI: 10.1186/s12905-020-00924-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful conservative treatment for massive uterine bleeding with non-septic disseminated intravascular coagulation after termination of early pregnancy in a woman with huge adenomyosis: case report

Abstract: Background: Adenomyosis is a benign gynecological condition in which endometrial tissue or endometrial-like tissue develops within the uterine myometrium. Few cases of disseminated intravascular coagulation has been reported in the patients with adenomyosis. Although hysterectomy is indicated for refractory massive uterine bleeding in the patients with advanced uterine adenomyosis, conservative treatment is often desired in women in the late reproductive age. Recently such cases are increasing due to the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Among potential agents, nafamostat mesylate (hereafter nafamostat), a serine protease inhibitor, could be one of the promising agents for treating COVID-19. Nafamostat, which provides sufficient prolongation of activated partial thromboplastin time (APTT) without causing major bleeding complications, has been used as an anticoagulant for hemodialysis procedures and disseminated intravascular coagulation (DIC) in Japan and South Korea [12,13]. Previous in vitro studies revealed that nafamostat blocks the entry of SARS-CoV-2 into the human cell by preventing the fusion of the envelope of SARS-CoV-2 with the host cell [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among potential agents, nafamostat mesylate (hereafter nafamostat), a serine protease inhibitor, could be one of the promising agents for treating COVID-19. Nafamostat, which provides sufficient prolongation of activated partial thromboplastin time (APTT) without causing major bleeding complications, has been used as an anticoagulant for hemodialysis procedures and disseminated intravascular coagulation (DIC) in Japan and South Korea [12,13]. Previous in vitro studies revealed that nafamostat blocks the entry of SARS-CoV-2 into the human cell by preventing the fusion of the envelope of SARS-CoV-2 with the host cell [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…5 We also reported a case of uterine adenomyosis with severe hemorrhage due to disseminated intravascular coagulation (DIC) with activated fibrinolysis on day 3 after elective abortion. 7 In this case, coagulation and the fibrinolytic function were activated without a decrease in the blood antithrombin III level, unlike septic DIC. Thus, some uterine adenomyosis may activate the coagulation/fibrinolytic system at the time of withdrawal bleeding or after the termination of pregnancy.…”
Section: Introductionmentioning
confidence: 72%
“…This pathophysiology of adenomyosis is drawing renewed attention. [3][4][5][6][7] We have previously reported that adenomyosis is associated with an increased risk of abnormal coagulation and fibrinolysis in the menstrual period. 5 We also reported a case of uterine adenomyosis with severe hemorrhage due to disseminated intravascular coagulation (DIC) with activated fibrinolysis on day 3 after elective abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Nafamostat is a broad-spectrum serine protease inhibitor possessing significant anti-coagulant and anti-inflammatory effects that help in inhibiting coagulation factor X, coagulation factor XII, prothrombin, Kallikrein-1, Trypsin 1, and ICAM-1 (Kim et al 2016 ). Approved in South Korea and Japan to treat disseminated intravascular coagulation [DIC], pancreatitis and for hemodialysis procedures, nafamostat is a promising agent for the treatment of COVID-19 (Choi and Kang 2015 ; Kimura et al 2020 ). It blocks the entry of SARS-CoV-2 inside the host cell by preventing the fusion of the virus envelope with the human cell (Hoffmann et al 2020c ; Yamamoto and Kiso 2020 ).…”
Section: Potential Covalent Spike Protein Inhibitorsmentioning
confidence: 99%